Pengaruh Kompensasi Lauk Pauk, Motivasi Dan Disiplin Kerja Terhadap Kinerja Karyawan - Khoriati Cahya Prihatin; Hadi Sunaryo (UNIVERSITAS ISLAM MALANG, 2018)
ABSTRACT Compensation, Motivation, Work Discipline interesting variables to study because these variables aim to increase the role and function of a human resource so that employee performance goes well and reaches every organizational goal. This study aims to find out: (1) Description of compensation for side dishes, motivation and work discipline on employee performance. (2) The effect of side dishes compensation on employee performance. (3) Effect of motivation on employee performance. 4) Effect of work discipline on employee performance. (5) Effect of side dishes compensation, motivation and work discipline simultaneously on employee performance. This research is a quantitative research using multiple linear regression analysis. Population and sample are all employees totaling 41 employees. The scale used is a Likert scale. Data collection techniques using a questionnaire method. The results of the descriptive analysis in this study indicate (1) Compensation for side dishes, motivation and work discipline on the performance of the employees is quite good. (2) There is a significant positive influence on the compensation variable for employee performance. (3) There is a significant positive influence on motivation variables on employee performance variables. (4) There is a significant positive influence on the variables of work discipline on employee performance variables. (5) There is a significant positive effect jointly compensation for side dishes, motivation and work discipline on employee performance. Based on the description above, the researcher suggests: (1) To maintain and increase employee performance, it is necessary to improve compensation for side dishes, motivation, and work discipline to employees. (2) it is expected that the Management can make this research as a consideration to determine the direction of improving employee performance both in terms of facilities such as added facilities and infrastructure, as well as improvements in terms of compensation, motivation and work discipline. Keyword: Side Dish Compensation, Motivation, Work Discipline, Employee Performance